Indonesia Sustainability Reporting Standard: What Needs to be Improved? - Iman Prihandono; Dewi S. Yuniarti (International Law Department, Faculty of Law Universitas Padjadjaran, 2023)
Responsible economic growth is an integral part of the goal of sustainable development. This transition to sustainable development needs to be based on a change in the mindset of business actors that business activities will be better and more sustainable if they pay attention to social, environmental and governance aspects (ESG). Recent data shows that there is a predicted increase of ESG investment by the end of 2021 by 73%, with a global fund asset being expected to reach 18 trillion in 2021. In line with this understanding, Financial Services Authority (OJK) have previously released the Sustainable Finance Roadmap Phase I (2015 - 2019) which aims to increase the understanding and capacity of business actors to move towards a sustainable economy. One significant output of the Roadmap is the issuance of OJK Regulation No. 51/POJK.03/2017 on the Implementation of Sustainable Finance, which stipulates the obligation for Financial Service Institutions, Issuers, and Public Companies to submit sustainability report. To accelerate the transition to a sustainable economy, OJK has recently issued the Sustainable Finance Roadmap Phase II (2021-2025), which focuses on ESG-based business development. This paper seeks to examine the comparison between the sustainability reporting obligation under the OJK Roadmaps with global ESG instruments, including United Nations Principles for Responsible Investment (UNPRI), Global Reporting Initiative (GRI), and the European Union Directive on Non-Financial Reporting, and to analyse whether OJK Roadmap II has accommodated the interest of global investors in light of ESG Investment, particularly reliable ESG reporting obligation by companies listed in the Indonesia Stock Exchange. It will conclude with a comprehensive evaluation of aspects needed to be improved by the existing Roadmap II to increase ESG investment in Indonesia.